2015
DOI: 10.1104/pp.15.00481
|View full text |Cite
|
Sign up to set email alerts
|

TRANSCRIPTION ACTIVATOR-LIKE EFFECTOR NUCLEASE-Mediated Generation and Metabolic Analysis of Camalexin-Deficient cyp71a12 cyp71a13 Double Knockout Lines

Abstract: In Arabidopsis (Arabidopsis thaliana), a number of defense-related metabolites are synthesized via indole-3-acetonitrile (IAN), including camalexin and indole-3-carboxylic acid (ICOOH) derivatives. Cytochrome P450 71A13 (CYP71A13) is a key enzyme for camalexin biosynthesis and catalyzes the conversion of indole-3-acetaldoxime (IAOx) to IAN. The CYP71A13 gene is located in tandem with its close homolog CYP71A12, also encoding an IAOx dehydratase. However, for CYP71A12, indole-3-carbaldehyde and cyanide were ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 44 publications
1
53
0
Order By: Relevance
“…In a previous study, Arabidopsis cyp71a12 cyp71a13 double knockout plants were generated using genome-editing tools. This finding supports that artificial nucleases, such as transcription activator-like effector nuclease (TALEN), will be useful in the generation of multigene knockout lines of linked genes [15]. The generation of double knockout plants using genomeediting tools and analysis of these plants are ongoing, and will be the subject of future research efforts in our lab.…”
Section: Discussionmentioning
confidence: 73%
“…In a previous study, Arabidopsis cyp71a12 cyp71a13 double knockout plants were generated using genome-editing tools. This finding supports that artificial nucleases, such as transcription activator-like effector nuclease (TALEN), will be useful in the generation of multigene knockout lines of linked genes [15]. The generation of double knockout plants using genomeediting tools and analysis of these plants are ongoing, and will be the subject of future research efforts in our lab.…”
Section: Discussionmentioning
confidence: 73%
“…Metabolite profiling of cyp 7 1A12 knockout plants indicates the crucial contribution of CYP71A12 monooxygenase to the AgNO 3 ‐, UV‐ and pathogen‐triggered accumulation of ICAs (Müller et al ., ; Rajniak et al ., ). Analysis of the double cyp71A12/A13 mutant suggested that CYP71A13 provides an additional minor contribution to the UV‐induced accumulation of these compounds (Müller et al ., ). To assess the role of both monooxygenases in the pathogen‐triggered biosynthesis of ICA derivatives, we inoculated leaves of cyp71A12 , cyp7A13 and cyp71A12/A13 mutant lines together with wild‐type (WT) plants (Col‐0 ecotype) with a spore suspension of the host‐adapted pathogenic strain of the necrotrophic fungus Plectosphaerella cucumerina BMM ( PcBMM ), which is able to colonize Col‐0 plants (Ton & Mauch‐Mani, ).…”
Section: Resultsmentioning
confidence: 99%
“…The TALEN‐generated cyp71A12 cyp71A13 was described by Müller et al . (). The myb34/51/122 triple mutant line was reported by Frerigmann et al .…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations